0‐1 Knapsack problem driven resource scheduling in caching‐enabled network: A case study on sports video. Issue 5 (9th May 2021) - Xu, Qiang
Abstract : In caching‐enabled network (CEN), the cache resources are very limited and expensive, thus it needs to make the exact scheduling for these cache resources. The cache resources in CEN are usually stored in the buffer/segment form, that is, with integer feature. Therefore, this paper plans to convert the cache resource scheduling into a 0‐1 knapsack problem (KP01) with a given total cache budget. For the solution procedure of KP01, it includes two stages. At first, some cache segments are locked in advance, where ant colony optimization is adopted for this. Then, the rest cache segments are evaluated in turn based on expectation efficiency, and some cache segments with high expectation efficiency value are locked. For the proposed resource scheduling strategy in CEN, this paper makes a detailed case study by considering a hot application, that is, sports video transmission, including two parts. On one hand, a concrete example is established to illustrate the correctness of cache resource scheduling. On the other hand, two baselines are added to prove the efficiency of cache resource scheduling by introducing lots of sports videos. All experiments are driven over NS3, and the results are considerably satisfactory. Abstract : At first, some cache segments are locked in advance, where ant colony optimization is used to determine the number of cache segments. Then for the rest cache segments, an expectation efficiency model is used to evaluate each cache segment's potential, where some cache segments with high expectation efficiency value are locked.